(untitled) (International Journal of Multidisciplinary Perspectives in Higher Education, 2020)
COVID-19 has forever changed the trajectory of higher education and the delivery of services, particularly at Historically Black Colleges and Universities (HBCUs). Therefore, how HBCUs strategically transform their campus operations with limited resources and remain competitive is vital to their survival. Considering these challenges, examining the role of governance and leadership and their decision-making processes in order to transition every aspect of their instructional services will be critical to the sustainability of these institutions. This essay examines a gap in the body of knowledge related to HBCU governance and leadership during COVID-19 and the considerations encompassing effective leadership during times of crisis.